EPIDEMIOLOGI MOLEKULER Clostridium difficile PADA ANAK DENGAN KEGANASAN - Soumena, Rifah Zafarani; Matinahoru, Marissa (Molucca Medica, 2024)
Background: Molecular epidemiology is a discipline that uses the tools of molecular microbiology to study the distribution and determinants of disease in human and animal populations. The goal of molecular epidemiology is to help explain the route taken by an epidemic by tracking the relevant unit of analysis, the entity responsible for the epidemic. The incidence of Clostridium difficile infection in children with malignancy is reported to be higher than in children without malignancy. C. difficile infection is a huge burden on the health care system. It is therefore important to identify the epidemic type as quickly as possible using molecular epidemiology. Strains circulating in Asia, as in other regions, have the potential to spread internationally, warranting close monitoring of the prevalence and molecular epidemiology of C. difficile infections in the region. However, research on C. difficile infection in children with malignancy is still very limited. Objective: to explain the role of molecular epidemiology through molecular diagnostic tools using PCR techniques on the severity of clinical symptoms of C. difficile infection in children with malignancy. Conclusion: Molecular diagnostic tools can be used in epidemiological research to recognize and determine the types of strains that are distributed throughout the world. From various studies previously described, it was found that different strains of C. difficile can produce different manifestations.